The Impact of Infrastructure Investment on Economic Growth in United Arab Emirates - Bouhitem, Mustapha (2011)
Abstract United Arab Emirates is one of fastest growing country in the world and one of the determining factors of UAE`s growth has been infrastructure investment. UAE`s sustained high growth has been supported by large infrastructure investment. In this context, we investigate the impact of infrastructure investment on economic growth in United Arab Emirates for the period 1975-2008. Overall, the results indicates positive and statistically significant impact of public/private capital, telephone line (both fixed and mobiles) and total length of roads on economic growth in UAE. Further, the results reveal that telephone line and total length of roads are the most important infrastructure indices affecting economic growth in UAE. The experience from UAE suggests that it is crucial to apply an economic policy that improves physical infrastructure in order to sustain high growth.